2001
DOI: 10.1042/bst029a029c
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding peroxisomal α-methylacyl-CoA racemase cause adult-onset sensory motor neuropathy

Abstract: The rat liver carnitine palmitoyltransferase 1 (L-CPTl) is the key regulatory enzyme of fatty acid oxidation in the liver, with malonyl-CoA acting as a physiological inhibitor. L-CPT1 is anchored into the outer mitochondria1 membrane (OMM) with a Ncyto-Ccyto topology by two transmembrane domains located within the N-terminal domain (residues 1 to 148). We have previously shown that this domain contains all of the informations for targeting the protein to the mitochondria. Moreover, replacement of the N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(80 citation statements)
references
References 0 publications
2
78
0
Order By: Relevance
“…20 The biochemical defect in this case has only recently been characterised as an absence of the α-methylacyl-CoA racemase. 16 There is stereoselectivity of the α-methyl branched acyl CoA esters and the bile acid intermediates, and these must be converted to their S forms before degradation by peroxisomal β-oxidation. Absence of the racemase has the same consequences as a deficiency of the branched chain acyl-CoA oxidase, although in the second R and S stereoisomers accumulate, and in racemase deficiency only R isomers accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…20 The biochemical defect in this case has only recently been characterised as an absence of the α-methylacyl-CoA racemase. 16 There is stereoselectivity of the α-methyl branched acyl CoA esters and the bile acid intermediates, and these must be converted to their S forms before degradation by peroxisomal β-oxidation. Absence of the racemase has the same consequences as a deficiency of the branched chain acyl-CoA oxidase, although in the second R and S stereoisomers accumulate, and in racemase deficiency only R isomers accumulate.…”
Section: Discussionmentioning
confidence: 99%
“…All patients manifest the neurological deficiencies but only some patients have symptoms of liver failure, 23 probably due to excretion of C27 bile acid intermediates into bile. [24][25][26] Effective therapy for D-bifunctional protein deficiency has not yet been reported.…”
Section: Cyp7a1 Deficiencymentioning
confidence: 99%
“…It is thought that the bile acid intermediates that are substrates for these enzymes can function as bile acids. 24 Both enzymes are not only involved in bile acid synthesis but also act on branched chain fatty acids such as pristanic acid. This explains the accumulation of pristanic acid in both disorders.…”
Section: Common Denominators Of Bile Acid Biosynthesis Defectsmentioning
confidence: 99%
“…This is thought to be a consequence of sustained rises in plasma branched chain fatty acids, such as pristinic acid. 13 With respect to prostate cancer, Zheng and colleagues 14 found that particular sequence variants in the AMACR gene strongly co-segregate with prostate cancer development in families affected by hereditary prostate cancer. It is also known that men who consume diets rich in dairy products and red meat are at increased risk for developing prostate cancer.…”
Section: Physiological Function Of Amacr/p504s and Its Potential Rolementioning
confidence: 99%